AWS Certified Database - Specialty (DBS-C01) Certification Guide : a Comprehensive Guide to Becoming an AWS Certified Database Specialist. - Gawron, Kate (Packt Publishing, Limited, 2022)
Pass the AWS Certified Database- Specialty Certification exam with the help of practice tests Key Features Understand different AWS database technologies and when to use them Master the management and administration of AWS databases using both the console and command line Complete, up-to-date coverage of DBS-C01 exam objectives to pass it on the first attempt Book Description The AWS Certified Database - Specialty certification is one of the most challenging AWS certifications. It validates your comprehensive understanding of databases, including the concepts of design, migration, deployment, access, maintenance, automation, monitoring, security, and troubleshooting. With this guide, you'll understand how to use various AWS databases, such as Aurora Serverless and Global Database, and even services such as Redshift and Neptune. You'll start with an introduction to the AWS databases, and then delve into workload-specific database design. As you advance through the chapters, you'll learn about migrating and deploying the databases, along with database security techniques such as encryption, auditing, and access controls. This AWS book will also cover monitoring, troubleshooting, and disaster recovery techniques, before testing all the knowledge you've gained throughout the book with the help of mock tests. By the end of this book, you'll have covered everything you need to pass the DBS-C01 AWS certification exam and have a handy, on-the-job desk reference guide. What you will learn Become familiar with the AWS Certified Database - Specialty exam format Explore AWS database services and key terminology Work with the AWS console and command line used for managing the databases Test and refine performance metrics to make key decisions and reduce cost Understand how to handle security risks and make decisions about database infrastructure and deployment Enhance your understanding of the topics you've learned using real-world hands-on examples Identify and resolve common RDS, Aurora, and DynamoDB issues Who this book is for This AWS certification book is for database administrators and IT professionals who perform complex big data analysis as well as students looking to get AWS Database Specialty certified. A solid understanding of cloud computing, specifically AWS services, is a must. Knowledge of basic administration tasks such as logging in and running SQL queries will be helpful.